2019
DOI: 10.21203/rs.2.15572/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of alternate-day fasting on body weight and dyslipidaemia in patients with non-alcoholic fatty liver disease: a randomised controlled trial

Abstract: Background: Alternate-day fasting (ADF) is a novel diet therapy that may achieve reduction in body weight and improvement of dyslipidaemia, but the impact of this diet on patients with non-alcoholic fatty liver disease (NAFLD) remains unknown. The aim of this study was to evaluate the effects of ADF on the body weight and lipid profile of individuals with NAFLD. Methods: NAFLD patients (n=271) were randomised to the ADF group, time-restricted feeding (TRF) group, or the control group and subjected to the resp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Johari et al 69 applied a modified alternate‐day calorie restriction (ie 70% calorie‐restriction on fasting day, ad‐libitum eating on non‐fasting day) to demonstrate an improvement in ALT levels as well as LSM and sonographically assessed steatosis 69 . Another study showed a decrease in BMI and triglyceride levels following 12 weeks of ADF or time‐restricted feeding (energy intake only during an 8h‐window each day) despite no changes in LSM 70 . Finally, Holmer et al 71 compared ICR on two non‐consecutive days/week (ie 5:2 diet, <500/600 kcal/d) vs a LCD/HFD in patients with NAFLD.…”
Section: Types Of Dietmentioning
confidence: 99%
“…Johari et al 69 applied a modified alternate‐day calorie restriction (ie 70% calorie‐restriction on fasting day, ad‐libitum eating on non‐fasting day) to demonstrate an improvement in ALT levels as well as LSM and sonographically assessed steatosis 69 . Another study showed a decrease in BMI and triglyceride levels following 12 weeks of ADF or time‐restricted feeding (energy intake only during an 8h‐window each day) despite no changes in LSM 70 . Finally, Holmer et al 71 compared ICR on two non‐consecutive days/week (ie 5:2 diet, <500/600 kcal/d) vs a LCD/HFD in patients with NAFLD.…”
Section: Types Of Dietmentioning
confidence: 99%
“…In a Malaysian study, 8 weeks of intermittent fasting with alternate-day calorie restriction resulted in the reduction of body weight and liver enzymes as well as liver steatosis and stiffness compared to a habitual diet [46]. A larger Chinese RCT randomized 271 MAFLD patients to undergo intermittent fasting, time-restricted feeding, or no intervention [20]. Both intermittent fasting and BCAAs, branched-chain amino acids; LES, late evening snack; HCC, hepatocellular carcinoma; ONS, oral nutritional supplementation; PNS, parenteral nutritional supplementation time-restricted feeding induced significant weight loss of 5.4% and 4.3%, respectively, while LDL, fasting insulin, and liver stiffness did not differ significantly between groups.…”
Section: Intermittent Energy Restriction: Intermittent Fasting and Time-restricted Feedingmentioning
confidence: 99%
“…Another study showed that respiratory quotient (RQ) after an overnight fast is lower in cirrhotic patients as compared to normal person, reflecting catabolism and an accelerated fat oxidation [4]. Another research showed the positive effects of alternate day fasting in patients with Non-alcoholic fatty liver disease (NAFLD) and led to weight loss, improvement in the dyslipidaemia within 12 weeks [5].…”
Section: Editorialmentioning
confidence: 99%